The Impact of Music in Improving English Speaking Fluency - Yulia Kaswari; Rohima Nurfarahin Fairus; M. Anan Abdullah; Selamet Riadi Jaelani (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
By exploring how music aids in vocabulary acquisition, this study aims to determine the potential benefits of incorporating musical elements in English language classrooms. Its purpose is to assess whether pupils truly comprehend the techniques for employing students’ pronounce. The participants in this study were 50 second semester English majors at Hamzanwadi University. Because random sampling chooses samples at random, giving every member of the population an equal chance to be chosen, this study used random sampling to eliminate data bias. The investigation was qualitative. The qualitative descriptive method was employed by the researcher. To obtain competent data, the researcher conducted observations to evaluate students' ability by allowing them to recount repeated episodes and events from the past. Its purpose is to assess whether pupils truly comprehend the techniques for employing students’ pronounce.